A co-design living labs philosophy of practice for end-to-end research design to translation with people with lived-experience of mental ill-health and carer/family and kinship groups - Palmer, Victoria J.; Bibb, Jennifer; Lewis, Matthew; Densley, Konstancja; Kritharidis, Roxanne; Dettmann, Elise; Sheehan, Pam; Daniell, Ann; Harding, Bev; Schipp, Tricia; Dost, Nargis; McDonald, Gregor (Frontiers in Public Health, 2023)
There is increased recognition that people with lived-experience of mental ill-health ought to be centred within research design, implementation and translation, and quality improvement and program evaluation of services. There is also an increased focus on ways to ensure that co-design processes can be led by people with lived-experience. Despite this, there remains limited explanation of the physical, social, human and economic infrastructure needed to create and sustain such models in research and service settings. This is particularly pertinent for all health service sectors (across mental and physical health and social services) but more so across tertiary education settings where research generation occurs for implementation and translation activities with policy and services. The Co-Design Living Labs program was established in 2017 as an example of a community-based embedded approach to bring people living with trauma and mental ill-health and carers/family and kinship group members together with university-based researchers to drive end to end research design to translation in mental health care and research sectors, the program’s current membership is near to 2000 people. This paper traces the evolution of the program in the context of the living labs tradition of open innovation. It overviews the philosophy of practice for working with people with lived-experience and carer/family and kinship group members—togetherness by design. Togetherness by design centres an ethical relation of being-for that moves beyond unethical and transactional approaches of being-aside and being-with as articulated by sociologist Zygmunt Bauman. The retrospective outlines how an initially researcher driven model, can evolve and transform to become one where people with lived-experience of mental ill-health and carer/family kinship group members hold clear decision-making roles, share in power to enact change and move into co-researcher roles within research teams. Eight mechanisms are presented in the context of an explanatory theoretical model of change for co-design and coproduction which are used to frame research co-design activities and provide space for continuous learning and evolution of the Co-Design Living Labs program.